(untitled) (Journal of International Crisis and Risk Communication Research, 2020)
Risk and crisis communication is a vibrant and growing area of research and practice. As we head into the third year of publishing the first journal dedicated to crisis and risk communication, the editor and editorial assistant pose some especially promising areas for future research. In this essay, we also introduce the articles published in this journal, including how they meet promising research gaps to fill.